1993
DOI: 10.1111/j.1440-169x.1993.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐peptide Antibody Identifies a 57 kDa Protein Tyrosine Kinase in the Sea Urchin Egg Cortex

Abstract: The egg plasma membrane and cortical structures are highly enriched in protein tyrosine kinase activity which is thought to play an important role in the fertilization process. In order to identify the tyrosine protein kinases in the egg cortex, a site directed polyclonal antibody was produced against a peptide duplicating a conserved region of the catalytic domain of the sea urchin c-abl gene product. The region chosen as an antigen had a high degree of homology (57%) to other protein tyrosine kinases. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The enzyme was identified by an antibody against the synthetic peptide corresponding to residues Thr-Tyr-Thr-Ala-Gln-Ala-Gly-AlaLys-Asn-Pro-Ile-Lys-Trp (a part of the IDA region) of the sea urchin c-Abl. They also found that the binding of the antibody completely inhibited the kinase activity (36). These conflicting results concerning the effect of antibody on the kinase activity might be explained by the difference in the epitopes that are recognized by these anti-IDA antibodies.…”
Section: Fig 7 Tyrosine Phosphorylation and Translocation Of The P57mentioning
confidence: 99%
See 4 more Smart Citations
“…The enzyme was identified by an antibody against the synthetic peptide corresponding to residues Thr-Tyr-Thr-Ala-Gln-Ala-Gly-AlaLys-Asn-Pro-Ile-Lys-Trp (a part of the IDA region) of the sea urchin c-Abl. They also found that the binding of the antibody completely inhibited the kinase activity (36). These conflicting results concerning the effect of antibody on the kinase activity might be explained by the difference in the epitopes that are recognized by these anti-IDA antibodies.…”
Section: Fig 7 Tyrosine Phosphorylation and Translocation Of The P57mentioning
confidence: 99%
“…As to the effect of the antibody on the kinase activity, Casnellie et al (35) reported that the Lck activity was inhibited by their antibody. Recently, Peaucellier et al (36) identified a 57-kDa protein-tyrosine kinase in sea urchin eggs. The enzyme was identified by an antibody against the synthetic peptide corresponding to residues Thr-Tyr-Thr-Ala-Gln-Ala-Gly-AlaLys-Asn-Pro-Ile-Lys-Trp (a part of the IDA region) of the sea urchin c-Abl.…”
Section: Fig 7 Tyrosine Phosphorylation and Translocation Of The P57mentioning
confidence: 99%
See 3 more Smart Citations